Does classification of persons with fibromyalgia into Multidimensional Pain Inventory subgroups detect differences in outcome after a standard chronic pain management program? - Verra, Martin L (Pulsus Group Inc, 2009)
INTRODUCTION: The present study aimed to replicate and validate the empirically derived subgroup classification based on the Multidimensional Pain Inventory (MPI) in a sample of highly disabled fibromyalgia (FM) patients. Second, it examined how the identified subgroups differed in their response to an intensive, interdisciplinary inpatient pain management program. METHODS: Participants were 118 persons with FM who experienced persistent pain and were disabled. Subgroup classification was conducted by cluster analysis using MPI subscale scores at entry to the program. At program entry and discharge, participants completed the MPI, Medical Outcomes Study Short Form-36, Hospital Anxiety and Depression Scale and Coping Strategies Questionnaire. RESULTS: Cluster analysis identified three subgroups in the highly disabled sample that were similar to those described by other studies using less disabled samples of FM. The dysfunctional subgroup (DYS; 36% of the sample) showed the highest level of depression, the interpersonally distressed subgroup (ID; 24%) showed a modest level of depression and the adaptive copers subgroup (AC; 38%) showed the lowest depression scores in the MPI (negative mood), Medical Outcomes Study Short Form-36 (mental health), Hospital Anxiety and Depression Scale (depression) and Coping Strategies Questionnaire (catastrophizing). Significant differences in treatment outcome were observed among the three subgroups in terms of reduction of pain severity (as assessed using the MPI). The effect sizes were 1.42 for DYS, 1.32 for AC and 0.62 for ID (P=0.004 for pairwise comparison of ID-AC and P=0.018 for ID-DYS). DISCUSSION: These findings underscore the importance of assessing individuals’ differences in how they adjust to FM.